Highly Efficient Ultrasound-Assisted Anthocyanin Extraction for Colorimetric Sensors and Drug Delivery Systems in Wound Dressings - Vilcahuamán, K.; Elgegren, M.; Kim, S.; Nakamatsu, J. (Springer Science and Business Media Deutschland GmbH, 2025)
Anthocyanins were extracted from Peruvian purple cabbage (PC) using ultrasonication, a greener and more efficient technique. The anthocyanin extract was incorporated into polymeric alginate membranes to obtain a pH-sensitive biosensor to monitor wound healing processes and drug delivery. The halochromic behavior was tested in five different acidic media (pH 4, 5, 6, 7, and 8) giving a differential colour for each. The antioxidant capacity of the PC extract was evaluated using the ABTS discoloration assay. A 1% (w/v) solution of the lyophilized extract resulted in 55.17 ± 0.46 TEAC mg/g. Phenolic content and equivalents of cyanidin-3-glucoside were evaluated using the Folin-Ciocalteu and pH differential assays, respectively, resulting in 36.1 ± 0.55 GAE mg and 8.63 ± 0.54 of C-3-G mg per gram of lyophilized extract, respectively. Finally, the PC extract was embedded in alginate (AL) membranes and characterized by contact angle and transparency.
Keywords: Drug delivery; Anthocyanin; Extraction (chemistry); Drug; Biomedical engineering; Medicine; Nanotechnology; Materials science; Pharmacology; Chemistry; Chromatography; Food science; https://purl.org/pe-repo/ocde/ford#2.09.00